STRATEGI DAN IMPLEMENTASI PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI PERGURUAN TINGGI - Aries Sundoro; Novi Irwansyah; Aries Setiawan; Lesna Purnawan; Kuntartoadi Twijugo (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Enhancing the quality of human resources (HR) in higher education is a crucial factor in supporting the excellence of teaching, research, and community service. This study aims to identify effective strategies and implementations for HR development within universities. A descriptive qualitative method was used, employing a case study approach in several higher education institutions in Indonesia. The findings reveal that HR quality improvement strategies include faculty training and competency development, academic degree advancement, implementation of a reward and punishment system, and strengthening a professional work culture. Implementation of these strategies faces several challenges, such as budget constraints, resistance to change, and the lack of integrated HR management. Nevertheless, with visionary leadership and institutional policy support, HR development can be pursued sustainably. This study recommends the importance of synergy among university leaders, faculty members, and administrative staff in fostering a conducive work environment for HR quality enhancement. Keywords: Human Resource Quality, Higher Education, Strategy, Implementation   Abstrak: Meningkatkan kualitas sumber daya manusia (SDM) di pendidikan tinggi merupakan faktor penting dalam mendukung keunggulan pengajaran, penelitian, dan pengabdian masyarakat. Studi ini bertujuan untuk mengidentifikasi strategi dan implementasi yang efektif untuk pengembangan SDM di dalam universitas. Metode kualitatif deskriptif digunakan, dengan menggunakan pendekatan studi kasus di beberapa institusi pendidikan tinggi di Indonesia. Temuan menunjukkan bahwa strategi peningkatan kualitas SDM meliputi pelatihan dan pengembangan kompetensi dosen, peningkatan gelar akademik, implementasi sistem penghargaan dan hukuman, dan penguatan budaya kerja profesional. Implementasi strategi ini menghadapi beberapa tantangan, seperti kendala anggaran, resistensi terhadap perubahan, dan kurangnya manajemen SDM yang terintegrasi. Namun demikian, dengan kepemimpinan visioner dan dukungan kebijakan institusional, pengembangan SDM dapat dilakukan secara berkelanjutan. Studi ini merekomendasikan pentingnya sinergi antara pimpinan universitas, anggota fakultas, dan staf administrasi dalam membina lingkungan kerja yang kondusif untuk peningkatan kualitas SDM. Kata kunci: Kualitas Sumber Daya Manusia, Pendidikan Tinggi, Strategi, Implementasi